T cell immune response predicts survival in severely ill COVID-19 patients requiring venovenous extracorporeal membrane oxygenation support - Ulakcsai, Zsuzsanna; Szabo, Liliana; Szabo, Zsofia; Karaszi, Eva; Szabo, Tamas; Fazekas, Levente; Vereb, Alexandra; Kovacs, Nora Fanna; Nemeth, Dora; Kovacs, Eniko; Nemeth, Endre; Nagy, Gyorgy; et al. (Frontiers in Immunology, 2023)
Introduction: There is a critical gap in understanding which SARS-CoV-2 patient would benefit most from venovenous extracorporeal membrane oxygenation (VV-ECMO) support. The potential role of a dysregulated immune response is still unclear in this patient population.Objectives: To assess the potential predictive value of SARS-CoV-2 specific cellular and humoral immune response for survival in critically ill COVID-19 patients requiring VV-ECMO.We conducted a prospective single-center observational study of unvaccinated patients requiring VV-ECMO support treated at the intensive care unit of Semmelweis University Heart and Vascular Center between March and December 2021. Peripheral blood samples were collected to measure the humoral and cellular immune status of the patients at the VV-ECMO cannulation. Patients were followed until hospital discharge.Results: Overall, 35 COVID-19 patients (63% male, median age 37 years) on VV-ECMO support were included in our study. The time from COVID-19 verification and to ECMO support was median (IQR) 10 (7-14) days. Nine (26%) patients were discharged alive and 26 (74%) deceased during their hospital stay. Immune tests confirmed ongoing SARS-CoV-2 infection in all patients, showing an increased humoral immune response. SARS-CoV-2specific cellular immune response was significantly higher among survivors compared to the deceased patients. Patients survived with higher probability with markers indicating higher T cell response detected by both QuantiFeron (QF) and flow cytometry (Flow) assays. (Flow S1 CD8+ ≥ 0.15%, Flow S1 CD4+ ≥ 0.02%, QF CD4 ≥ 0.07, QF whole genome ≥ 0.59). In univariate Cox proportional hazard regression analysis BMI, right ventricular (RV) failure, QF whole genome T cell level and Flow S1 CD8+ T cell level were associated with mortality, and we found that an increased T-cell response showed significant negative association with mortality, independent of BMI and RV failure.Evaluation of SARS-CoV-2 specific T cell response before the cannulation can aid the risk stratification and evaluation of seriously ill COVID-19 patients undergoing VV-ECMO support by predicting survival, potentially changing our clinical practice in the future.